Reactive ion beam figuring of optical aluminium surfaces. (30th January 2017) - Bauer, Jens; Frost, Frank; Arnold, Thomas
Abstract: Ultra-smooth and arbitrarily shaped reflective optics are necessary for further progress in EUV/XUV lithography, x-ray and synchrotron technology. As one of the most important technological mirror optic materials, aluminium behaves in a rather difficult way in ultra-precision machining with such standard techniques as diamond-turning and subsequent ion beam figuring (IBF). In particular, in the latter, a strong surface roughening is obtained. Hence, up to now it has not been possible to attain the surface qualities required for UV or just visible spectral range applications. To overcome the limitations mainly caused by the aluminium alloy structural and compositional conditions, a reactive ion beam machining process using oxygen process gas is evaluated. To clarify the principle differences in the effect of oxygen gas contrary to oxygen ions on aluminium surface machining, we firstly focus on chemical-assisted ion beam etching (CAIBE) and reactive ion beam etching (RIBE) experiments in a phenomenological manner. Then, the optimum process route will be explored within a more quantitative analysis applying the concept of power spectral density (PSD) for a sophisticated treatment of the surface topography. Eventually, the surface composition is examined by means of dynamic secondary ion mass spectrometry (SIMS) suggesting a characteristic model scheme for the chemical modification of the aluminium surface during oxygen ion beam machining. Monte Carlo simulations were applied to achieve a more detailed process conception.